PENGARUH AKAD PEMBIAYAAN WADIAH DAN MUDHARABAH TERHADAP PROFITABILITAS PADA BANK SYARIAH MANDIRI - Mufid Habib Mustofa; Jaenudin Jaenudin; Bustami Irvan Irvan (Institut Bisnis Muhammadiyah Bekasi, 2022)
This study aims to measure and find out how big an influence of wadi’ah financing and Mudarabah financing to the revenue at BSM (Bank Syariah Mandiri) Jakarta from the year 2008 until the end of 2017. This study uses the revenue multiple regression techniques which first learned of the requirement is made to know in order to be eligible. Variables t hitung -2.36 so that H 1 is accepted which means that partially wadiah influential variables significantly to profitability to the second hypothesis, namely that the values obtained mudharabah variable t hitung of 3.542 with t tabel of 0.1574 so because the value t hitung